1999
DOI: 10.1046/j.1365-2044.1999.01061.x
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphorus poisoning and anaesthesia

Abstract: SummaryOrganophosphorus compounds, used as insecticides and agents of chemical warfare, are a major global cause of health problems. These irreversible inhibitors of cholinesterase produce three wellrecognised clinical entities: the initial cholinergic phase, which is a medical emergency often requiring management in an intensive care unit; the intermediate syndrome, during which prolonged ventilatory care is necessary; and delayed polyneuropathy. In addition, disturbances of body temperature and endocrine fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
105
0
26

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(132 citation statements)
references
References 117 publications
(118 reference statements)
1
105
0
26
Order By: Relevance
“…It has been reported that IS can develop within first 96 hours of acute organophosphate poisoning (OP) (1,2). To the best of our knowledge, there is no reported case of IS developing over 96 hours after OP exposure.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that IS can develop within first 96 hours of acute organophosphate poisoning (OP) (1,2). To the best of our knowledge, there is no reported case of IS developing over 96 hours after OP exposure.…”
Section: To the Editormentioning
confidence: 99%
“…The most important initial sign of IS is respiratory failure (1)(2)(3)(4)(5). The muscle weakness begins at first in the extremities, the neck, the eyes, and the respiratory system (6).…”
Section: To the Editormentioning
confidence: 99%
“…Organophosphate intoxication may occur during agricultural spraying, transport of organophosphate compounds, or domestic accidents, although suicide attempts are the most common way of intoxication (2,3). Organophosphate intoxication may occur via oral, respiratory, transdermal, or parenteral route (4).…”
Section: Introductionmentioning
confidence: 99%
“…Death typically occurs within the first 24 hours, usually due to respiratory failure (3). Some complications of organophosphate intoxication have been reported, including "delayed organophosphateinduced polyneuropathy" that has been only rarely reported (2).…”
Section: Introductionmentioning
confidence: 99%
“…The role of cholinesterase estimations in anaesthetic practice will continue to be valuable, for these enzymes are necessary for the hydrolysis not only of succinylcholine and mivacurium, but also for that of diamorphine, cocaine, esmolol, remifentanil, procaine and related local analgesics. Cholinesterase concentrations may also be depressed by a wide range of therapeutic agents that may be prescribed for subjects presenting for anaesthesia [37].…”
mentioning
confidence: 99%